2010
DOI: 10.1016/j.neuroscience.2010.06.060
|View full text |Cite
|
Sign up to set email alerts
|

Neuroprotective properties of prostaglandin I2 IP receptor in focal cerebral ischemia

Abstract: We and others have identified that inhibition of cyclooxygenase might not be the optimal approach to limiting brain damage after stroke. Now we are investigating the unique properties of the various prostaglandin receptors to determine whether blocking those that mediate toxicity or stimulating those that reduce toxicity will improve neurological outcomes. Here, we determined the respective contribution of the prostaglandin I2 (PGI2) receptor in transient middle cerebral artery (MCA) occlusion (tMCAO) and perm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
21
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(22 citation statements)
references
References 37 publications
1
21
0
Order By: Relevance
“…It has also been reported that HO1 −/− and WT male mice show no differences in brain infarct volume in the tMCAO reperfusion model (Dore et al, 1999) of 1 h occlusion and 23 hr reperfusion whereas in pMCAO model it was demonstrated that after 7 days of ischemia, HO1 −/− male animals had significantly higher infarct volume as compared to WT male animals, suggesting a neuroprotective role of HO1(Shah et al, 2011). HO1 neuroprotective properties were also observed in NMDA-induced neurotoxicity model (Saleem et al, 2010) and after ischemic preconditioning, where male HO1 −/− mice did not shown any protection and suffered from higher brain damage as compared to WT after 48 hrs of permanent ischemia (Zeynalov et al, 2009). We recently reported that HO1 −/− male mice showed lower neurogenesis as compared to WT animals following permanent ischemia (Nada et al, 2014).…”
Section: Discussionmentioning
confidence: 95%
“…It has also been reported that HO1 −/− and WT male mice show no differences in brain infarct volume in the tMCAO reperfusion model (Dore et al, 1999) of 1 h occlusion and 23 hr reperfusion whereas in pMCAO model it was demonstrated that after 7 days of ischemia, HO1 −/− male animals had significantly higher infarct volume as compared to WT male animals, suggesting a neuroprotective role of HO1(Shah et al, 2011). HO1 neuroprotective properties were also observed in NMDA-induced neurotoxicity model (Saleem et al, 2010) and after ischemic preconditioning, where male HO1 −/− mice did not shown any protection and suffered from higher brain damage as compared to WT after 48 hrs of permanent ischemia (Zeynalov et al, 2009). We recently reported that HO1 −/− male mice showed lower neurogenesis as compared to WT animals following permanent ischemia (Nada et al, 2014).…”
Section: Discussionmentioning
confidence: 95%
“…13 The sizes of brain lesions in the saline group were consistent with those obtained by other researchers (25%-28% of ipsilateral hemisphere), demonstrating the reproducibility of focal ischemia induction. 14,15 Between 1980 and 2000 there were a few studies showing the effectiveness of CoQ10 in different animal models of brain damage. [16][17][18] However, most research used preventive administration of a large dose of CoQ10, and/ or its enteral administration.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, beraprost reduces the neurological deficit score and infarct volume after both transient and permanent middle cerebral artery occlusion in an adult mouse model. In these animal models of brain ischemia, PGI 2 probably protects neurons by enhancing intracellular cAMP production and reducing Ca 2ϩ overload in neurons to mitigate subsequent neuronal cell death (Saleem et al, 2010). Studies have also examined the potential IP receptor involved in the actions of PGI 2 after brain ischemia.…”
Section: E Prostacyclin Metabolism and Hypoxic Ischemic Encephalopatmentioning
confidence: 99%